Evaluation of Anesthetic Depth and Its Association with Postoperative Nausea, Pain, and Hospital Stay in General Surgery Patients - Tahir Hamid, Faisal Toheed, Mobasher Ahmad Saeed, Khushal Khan, Parkash Lal Lund, Abdul Sami Mirani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anesthetic depth is a critical component of intraoperative management that may significantly influence postoperative outcomes. Objective: This study aimed to evaluate the relationship between anesthetic depth, monitored using the Bispectral Index (BIS), and the incidence of PONV, postoperative pain, and length of hospital stay in patients undergoing general surgery. Methods: Patients were categorized into three groups based on intraoperative BIS scores: Group A (light anesthesia, BIS > 60), Group B (adequate anesthesia, BIS 40–60), and Group C (deep anesthesia, BIS < 40). Postoperative nausea was assessed within 24 hours using a 4-point scale. Pain intensity was evaluated using the Visual Analog Scale (VAS) at 2, 6, 12, and 24 hours postoperatively. Results: Group B (adequate anesthesia) showed the lowest incidence of PONV (27.3%), compared to Group A (50%) and Group C (68%) (p = 0.004). Mean VAS scores at all time points were significantly lower in Group B (p < 0.01). The mean hospital stay was also shortest in Group B (2.4 ± 0.8 days), compared to Group A (3.2 ± 1.0 days) and Group C (3.9 ± 1.2 days) (p = 0.002). Multivariate regression identified deep anesthesia (BIS < 40), presence of PONV, and high postoperative pain scores as significant predictors of prolonged hospitalization. Conclusion: Maintaining anesthetic depth within the optimal BIS range of 40–60 is associated with reduced postoperative complications and shorter hospital stay. Both light and deep anesthesia were linked to poorer outcomes, emphasizing the importance of individualized, depth-guided anesthesia monitoring for enhanced perioperative care and recovery. Keywords: Anesthetic depth, BIS monitoring, postoperative nausea, postoperative pain, hospital stay